2014
DOI: 10.1097/ajp.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pain in Fabry Disease

Abstract: Pain in Fabry disease affects both sexes and has a complex phenotype that requires comprehensive assessment. Current pain questionnaires fail to cover the entire scope of Fabry pain. Although basically neuropathic, some types of Fabry pain may respond to nonsteroidal antirheumatics and nonopioid analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
170
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(179 citation statements)
references
References 23 publications
4
170
0
5
Order By: Relevance
“…Fabry disease-associated pain is assumed to be neuropathic because Gb3 deposits have been reported in nervous tissue of patients [5,9] and because small-fiber neuropathy is associated with Fabry disease [2,10,11,16,19,20]. However, Fabry pain also entails nonneuropathic components and may respond to medication that is otherwise ineffective in neuropathic pain [18].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fabry disease-associated pain is assumed to be neuropathic because Gb3 deposits have been reported in nervous tissue of patients [5,9] and because small-fiber neuropathy is associated with Fabry disease [2,10,11,16,19,20]. However, Fabry pain also entails nonneuropathic components and may respond to medication that is otherwise ineffective in neuropathic pain [18].…”
Section: Introductionmentioning
confidence: 98%
“…Previously we showed that Fabry disease-associated pain mainly manifests with 4 distinct phenotypes: pain attacks, evoked pain (ie, pain induced by touch or normally nonpainful stimuli), pain crises, and permanent pain [6,18]. Fabry pain is mostly of a burning character; manifests at soles and palms; is triggerable by fever, heat, or physical activity; and has a diverse temporal course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabry-associated pain is often very complex and difficult to cope, requiring extensive assessment by specialized neurologists [6,8]. Neuropathic origin is regularly hypothesized [40] potentially explaining why patients might not respond to therapy with non-steroidal anti-rheumatic and/or non-opioid analgetic drugs, but from medications as pregabalin, carbamazepines or tricyclic antidepressants [41].…”
Section: Fabry-associated Painmentioning
confidence: 99%
“…In respective males with a classic mutation, a very low or completely missing α-GAL enzyme activity is apparent [1,2]. As a result, progressive globotriaosylceramides (Gb3) accumulation in lysosome-carrying tissues lead to irreversible and disease-specific tissue injury of the kidneys [3], heart [4] and equivalent alterations affecting the central and peripheral nervous system [5,6] (fig. 1).…”
Section: Introductionmentioning
confidence: 99%